PENERAPAN SOFTWARE MATLAB TERHADAP KEMAMPUAN MENYELESAIKAN MASALAH NUMERIK MAHASISWA JURUSAN PENDIDIKAN MATEMATIKA - Dindin Sobiruddin (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2014)
Numerical method is one of the subjects in mathematics education majors are discussed to solve the problem in numeric. It is different with the mathematic problem that can be solve by analysis and algebra by the algorithm and analysis. The software that can help undergraduate students’ solve the numerical problem is MATLAB. The advantages of MATLAB to solve the numerical problem are help students’ visualization graphs and train the reasoning abilities. The method used is experimental, with samples are undergraduate students mathematics education programm 8 semester academic year 2013/2014 as many as 94 students. The results showed an increase of undergraduate students ability on construct algorithms, solve the numerical problem after learning using MATLAB software, and compiling programming using MATLAB. In addition, students also showed a positive response to learning numerical methods using MATLAB software.